Design and performance analysis on heat pipe hydrostatic thrust bearings based on rectangular oil pad. Issue 7 (10th September 2018) - Li, Xibing; Li, Weixiang; Chen, Xueyong; Li, Ming; Chen, Huayun; Yue, Xin
Abstract : Purpose: The purpose of this paper is to examine the effect of application of a heat pipe in an aspect of hydrostatic thrust bearings on thermal balance and deformation and the role of this application in increasing the rotating speed of a workbench. Design/methodology/approach: Numerical simulations of oil film temperature field, the temperature field and thermal deformation of the bearing's workbench and base were performed by finite element analysis (FEA) software for both the traditional hydrostatic thrust bearings and the heat pipe ones. Findings: Oil pad and workbench of the hydrostatic thrust bearings are fabricated with a heat pipe cooling structure, which can take away most of the heat generated by shearing of the oil film, control the temperature rise and thermal deformation of the hydrostatic thrust bearing effectively, avoid the dry friction phenomenon and finally improve the processing quality of equipment. Originality/value: The heat pipe hydrostatic thrust bearings could control the temperature rise and thermal deformation of the hydrostatic thrust bearing effectively, avoid the dry friction phenomenon and improve the processing quality of equipment.